Google Cloud Certified Professional Cloud Network Engineer guide design, implement, manage, and secure a network architecture in Google Cloud - Ipsale, Maurizio; Gilioli, Mirko (Packt Publishing, 2022)
Gain practical skills to design, deploy, and manage networks on Google Cloud and prepare to gain Professional Cloud Network Engineer certification Key Features Gain hands-on experience in implementing VPCs, hybrid connectivity, network services, and security Establish a secure network architecture by learning security best practices Leverage this comprehensive guide to gain Professional Cloud Network Engineer certification Book DescriptionGoogle Cloud, the public cloud platform from Google, has a variety of networking options, which are instrumental in managing a networking architecture. This book will give you hands-on experience of implementing and securing networks in Google Cloud Platform (GCP). You will understand the basics of Google Cloud infrastructure and learn to design, plan, and prototype a network on GCP. After implementing a Virtual Private Cloud (VPC), you will configure network services and implement hybrid connectivity. Later, the book focuses on security, which forms an important aspect of a network. You will also get to grips with network security and learn to manage and monitor network operations in GCP. Finally, you will learn to optimize network resources and delve into advanced networking. The book also helps you to reinforce your knowledge with the help of mock tests featuring exam-like questions. By the end of this book, you will have gained a complete understanding of networking in Google Cloud and learned everything you need to pass the certification exam. What you will learn Understand the fundamentals of Google Cloud architecture Implement and manage network architectures in Google Cloud Platform Get up to speed with VPCs and configure VPC networks, subnets, and routers Understand the command line interface and GCP console for networking Get to grips with logging and monitoring to troubleshoot network and security Use the knowledge you gain to implement advanced networks on GCP Who this book is for This Google Cloud certification book is for cloud network engineers, cloud architects, cloud engineers, administrators, and anyone who is looking to design, implement, and manage network architectures in Google Cloud Platform. You can use this book as a guide for passing the Professional Cloud Network Engineer certification exam. You need to have at least a year of experience in Google Cloud, basic enterprise-level network design experience, and a fundamental understanding of Cloud Shell to get started with this book.